Gelastic seizures associated with hypothalamic hamartomas. An update in the clinical presentation, diagnosis and treatment - José F. Tellez-Zenteno (Dove Medical Press, 2008)
José F. Tellez-Zenteno1, Cesar Serrano-Almeida2, Farzad Moien-Afshari11Division of Neurology, University of Saskatchewan, Saskatoon, Saskatchewan, Canada; 2Department of Clinical Neurosciences, University of Calgary, Calgary, Alberta, CanadaAbstract: Gelastic seizures are epileptic events characterized by bouts of laughter. Laughter-like vocalization is usually combined with facial contraction in the form of a smile. Autonomic features such as flushing, tachycardia, and altered respiration are widely recognized. Conscious state may not be impaired, although this is often difficult to asses particularly in young children. Gelastic seizures have been associated classically to hypothalamic hamartomas, although different extrahypothalamic localizations have been described. Hypothalamic hamartomas are rare congenital lesions presenting with the classic triad of gelastic epilepsy, precocious puberty and developmental delay. The clinical course of patients with gelastic seizures associated with hypothalamic hamartomas is progressive, commencing with gelastic seizures in infancy, deteriorating into more complex seizure disorder resulting in intractable epilepsy. Electrophysiological, radiological, and pathophysiological studies have confirmed the intrinsic epileptogenicity of the hypothalamic hamartoma. Currently the most effective surgical approach is the trancallosal anterior interforniceal approach, however newer approaches including the endoscopic and other treatment such as radiosurgery and gamma knife have been used with success. This review focuses on the syndrome of gelastic seizures associated with hypothalamic hamartomas, but it also reviews other concepts such as status gelasticus and some aspects of gelastic seizures in other locations.Keywords: epilepsy, gelastic seizures, epilepsy surgery, hypothalamic hamartoma, intractable epilepsy